2012
DOI: 10.1103/physrevlett.108.185701
|View full text |Cite
|
Sign up to set email alerts
|

Disorder Promotes Ferromagnetism: Rounding of the Quantum Phase Transition inSr1xCaxRuO3

Abstract: The subtle interplay of randomness and quantum fluctuations at low temperatures gives rise to a plethora of unconventional phenomena in systems ranging from quantum magnets and correlated electron materials to ultracold atomic gases. Particularly strong disorder effects have been predicted to occur at zero-temperature quantum phase transitions. Here, we demonstrate that the composition-driven ferromagnetic-to-paramagnetic quantum phase transition in Sr(1-x)Ca(x)RuO3 is completely destroyed by the disorder intr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 31 publications
6
40
0
2
Order By: Relevance
“…This theory applies to the Sr 1−x Ca x RuO 3 system and successfully explains the dependence of the Ca concentration on the low-temperature dc magnetization data. 33) In Sr 1−x La x RuO 3 , however, the result (3) clearly contradicts this assumption, suggesting that the properties of cluster-glass states in Sr 1−x La x RuO 3 cannot be explained simply in terms of the distribution of La atoms in real space.…”
Section: Discussionmentioning
confidence: 94%
“…This theory applies to the Sr 1−x Ca x RuO 3 system and successfully explains the dependence of the Ca concentration on the low-temperature dc magnetization data. 33) In Sr 1−x La x RuO 3 , however, the result (3) clearly contradicts this assumption, suggesting that the properties of cluster-glass states in Sr 1−x La x RuO 3 cannot be explained simply in terms of the distribution of La atoms in real space.…”
Section: Discussionmentioning
confidence: 94%
“…22,23) Suppression of the ferromagnetism has also been found in the Sr site-substituted system Sr 1−x Ca x RuO 3 . [24][25][26][27][28][29] Substituting Ca for Sr increases the Ru-O-Ru bond angle and thereby enhances the RuO 6 octahedra rotation in the distorted perovskite structure. This variation is expected to strongly affect the electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent magnetization study has revealed that the ferromagnetic-to-paramagnetic quantum phase transition driven by the substitution is totally destroyed by the disorder, and the FM phase is extended to over a wide x range. 29) It is thus considered that both the electronic correlation and disorder play an important role in this system. Sr 1−x La x RuO 3 also shows a suppression of ferromagnetism generated by substituting La for Sr. 31,32) The La substitution also enhances the RuO 6 octahedra rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, T C is suppressed all the way to absolute zero on substitution of Sr 2 þ by the smaller Ca 2 þ ions at a critical concentration x c E0.7, where Sr 1 À x Ca x RuO 3 (SCRO) turns from a ferromagnetic (FM) to a paramagnetic ground state. Whether a quantum critical point (QCP) may be present at x c is a matter of current debate 2,4,7,8 . While specific heat 3 and NMR 4 measurements both concluded that the self-consistent renormalization theory 9 , equivalent to the Hertz-Millis model 10,11 , could describe the underlying physics of an FM QCP in SCRO, recent Kerr effect measurements on a composition-spread epitaxial film showed that a possible quantum phase transition (QPT) around a (reduced) critical concentration x c were smeared by disorder originating from the difference of ionic radii between Sr and Ca ions 8 .…”
mentioning
confidence: 99%
“…Whether a quantum critical point (QCP) may be present at x c is a matter of current debate 2,4,7,8 . While specific heat 3 and NMR 4 measurements both concluded that the self-consistent renormalization theory 9 , equivalent to the Hertz-Millis model 10,11 , could describe the underlying physics of an FM QCP in SCRO, recent Kerr effect measurements on a composition-spread epitaxial film showed that a possible quantum phase transition (QPT) around a (reduced) critical concentration x c were smeared by disorder originating from the difference of ionic radii between Sr and Ca ions 8 . In addition, on the basis of muon-spin-rotation (mSR) experiments, it was argued that a spontaneous phase separation may be a common feature in FM systems near their QPTs, leading to a suppression of dynamic critical behaviour 7,12 .…”
mentioning
confidence: 99%